2015
DOI: 10.5430/jst.v5n2p32
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT and MIBG scans in diagnosis and management of Neuroblastoma

Abstract: Introduction and aim: Several studies report conflicting results about 18 F-FDG/PET and MIBG scans and their diagnostic as well as prognostic significance in children with neuroblastoma. The current study was meant to evaluate both modalities and to compare them in relation to standardized modes of evaluation. Results: FDG/PET showed good results in detecting NB at all sites. FDG/PET also showed a higher sensitivity and specificity, and a better PPV/NPV than MIBG which was not statistically significant. Concor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Kushner and colleagues found that PET was equal to 123 I/ 131 I MIBG scans in detecting NB when including the skull in the comparison, but was superior in only extracranial skeletal structures [17]. Additionally, Fawzy et al suggested overall accuracy of 18 F-FDG PET/CT was slightly higher than MIBG in the detection of BMI with values of 66.6% and 66.3% [11]. In contrast, several studies showed that 123 I-MIBG scan was more sensitive in assessment of bony metastatic lesions than 18 F-FDG PET [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kushner and colleagues found that PET was equal to 123 I/ 131 I MIBG scans in detecting NB when including the skull in the comparison, but was superior in only extracranial skeletal structures [17]. Additionally, Fawzy et al suggested overall accuracy of 18 F-FDG PET/CT was slightly higher than MIBG in the detection of BMI with values of 66.6% and 66.3% [11]. In contrast, several studies showed that 123 I-MIBG scan was more sensitive in assessment of bony metastatic lesions than 18 F-FDG PET [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…ere were two studies evaluating the usefulness of FDG PET, with regard to detection of bone/BMI in pediatric NB patients. Moreover, one of the two studies focused on Fawzy et al [11] Gil et al [12] Ishiguchi et al [13] Tezol et al [14] Yagci-Kupeli et al [15] Zapata et al [16] Patient pretreatment patients, which reduced the number of false positives. Since it has been known that chemotherapy can stimulate hyperactivity in bone marrow, subgroup analysis performed by two different analysis types suggested that patient-based analysis showed a lower sensitivity but a higher specificity than those of lesion-based analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations